Lactate rewires lipid metabolism and sustains a metabolic-epigenetic axis in prostate cancer - Ippolito, Luigi (Cancer Res, 2022)
Lactate is an abundant oncometabolite in the tumor environment. In prostate cancer (PCa), cancer-associated fibroblasts are major contributors of secreted lactate, which can be taken up by cancer cells to sustain mitochondrial metabolism. However, how lactate impacts transcriptional regulation in tumors has yet to be fully elucidated. Here, we describe a mechanism by which CAF-secreted lactate is able to increase the expression of genes involved in lipid metabolism in PCa cells. This regulation enhanced intracellular lipid accumulation in lipid droplets (LD) and provided acetyl moieties for histone acetylation, establishing a regulatory loop between metabolites and epigenetic modification. Inhibition of this loop by targeting the bromodomain and extraterminal (BET) protein family of histone acetylation readers suppressed the expression of perilipin-2 (PLIN2), a crucial component of LDs, disrupting lactate-dependent lipid metabolic rewiring. Inhibition of this CAF-induced metabolic-epigenetic regulatory loop in vivo reduced growth and metastasis of prostate cancer cells, demonstrating its translational relevance as a therapeutic target in PCa. Clinically, PLIN2 expression was elevated in tumors with a higher Gleason grade and in castration resistant prostate cancer compared to primary PCa. Overall, these findings show that lactate has both a metabolic and an epigenetic role in promoting PCa progression.